(untitled) (Proceedings of International Educators Conference, 2024)
In this article, a moderate psychological environment in the family is the prerequisite for the formation of a healthy family, the formation of a healthy lifestyle among the population, the study of the woman’s genotype, the reaction of the immune system to various external influences. information provided.